Acting on the call for cervical cancer elimination: Planning tools for low- and middle- income countries to increase the coverage and effectiveness of screening and treatment - Tara Herrick; Kerry A. Thomson; Michelle Shin; Sarah Gannon; Vivien Tsu; Silvia de Sanjosé (BMC, 2022)
Abstract Introduction Accessible planning tools tailored for low-and middle-income countries can assist decision makers in comparing implementation of different cervical cancer screening approaches and treatment delivery scenarios in settings with high cervical cancer burden. Methods The Cervical Precancer Planning Tool (CPPT) was developed by PATH for users to explore and compare the accuracy of screening approaches, what treatment equipment to procure, and how best to deploy treatment equipment in a given country. The CPPT compares four screening approaches: 1) visual inspection with acetic acid (VIA), 2) HPV testing, 3) HPV testing followed by a VIA triage, and 4) HPV testing followed by an enhanced triage test. Accuracy of screening outcomes (e.g., true positives, false positives) is based on published sensitivity and specificity of tests to detect cervical precancerous lesions. The CPPT compares five scenarios for deploying ablative treatment equipment: 1) cervical precancer equipment at every location a woman is screened (single visit approach), 2) equipment only at a hospital level, 3) a single unit of equipment in each district, 4) allowing two districts to share a single unit of equipment, and 5) equipment placed at select district hospitals paired with mobile outreach. Users can customize the CPPT by adjusting pre-populated baseline values and assumptions, including population estimates, screening age range, screening frequency, HPV and HIV prevalence, supply costs, and health facility details. Results The CPPT generates data tables and graphs that compare the results of implementing each of the four screening and five treatment scenarios disaggregated by HIV status. Outputs include the number and outcomes of women screened, cost of each screening approach, provider time and cost saved by implementing self-sampling for HPV testing, number of women treated, treatment equipment needed by type, and the financial and economic costs for each equipment deployment scenario. Conclusion The CPPT provides practical information and data to compare tradeoffs of patient access and screening accuracy as well as efficient utilization of equipment, skilled personnel, and financial resources. Country decision makers can use outputs from the CPPT to guide the scale-up of cervical cancer screening and treatment while optimizing limited resources.